Essential Oils of Zingiber ottensii Valet. and Zingiber zerumbet (L.) Sm. from Sabah, Malaysia - Abd. Malek, Sri Nurestri; Ibrahim, Halijah; Lai, Hong Sok; Serm, Lee Guan; Seng, Chan Kam; Yusoff, Mashitah Mohd.; Mohd. Ali, Nor Azah (Malaysian Journal of Science, 2005)
The essential oils of Zingiber ottensii Valet. and Zingiber zerumbet (L.) Sm. from Sabah, Malaysia obtained by hydrodistillation of the fresh rhizomes were analyzed by a combination of capillary GC and GC-MS. Twenty-eight and eighteen components were identified from the rhizomes of Z. ottensii and Z. zerumbet respectively. The components were determined by comparing their Retention Indices with those reported in the literature and their mass spectral data with those from the mass spectral database. The most abundant component of Z. ottensii and Z. zerumbet rhizome oil was zerumbone representing 37% and 73% of the total oil respectively. Other major components of Z. ottensii were terpinen-4-ol (16.8%), Î±- humulene (10.9%) and sabinene (7.2%) whilst that of Z. zerumbet were Î±-humulene (5.9%), camphene (2.8%) and caryophyllene oxide (2.7%).